Effect of Three Light Curing Protocols and Load Cycling on Microleakage of Class V Composite Restorations - Davari, Abdolrahim; Daneshkazemi, Alireza; Taghizadeh, Tahere (Journal of Dental School, 2019)
Objective: Different methods have been suggested to overcome the polymerization shrinkage of composite restorations. Changing the light curing protocol to improve polymerization by using new light curing units is among these methods. The new devices are more efficient, portable and durable and produce less heat. This study aimed to assess the marginal microleakage of class V composite restorations subjected to three different light curing protocols and mechanical cycles. Methods: This was an in-vitro experimental study. Class V cavities measuring 2x3x1.5 mm were prepared on the buccal and lingual surfaces of 90 extracted human premolar teeth 1.5 mm above and below the cement enamel junction (CEJ). The samples were selected using convenience sampling and divided into 9 experimental groups of 10 each by using the Table of Random Numbers to control for the bias. The cavities were restored with packable composite resin along with Tetric-N- Bond and cured using three light curing protocols of conventional (680 mW/cm2 for 30s), soft-start (380 mW/cm2 for 10s followed by 680 mW/cm2 for 20s) and pulse (680 mW/cm2 for 30s,1s interval and 1s of lighting). The teeth were then subjected to mechanical cycles of 0, 500,000 and 1,000,000 and immersed in 2% Fuchsin for 24h. The teeth were then sectioned in half from the middle of the restoration buccolingually and the degree of microleakage was evaluated under a stereomicroscope (Zeiss, Germany) with 40X magnification. Data were analyzed using the Kruskal Wallis and the Mann-Whitney tests. Results: Despite the structural differences between the enamel and dentin margins, no significant difference was found in the degree of microleakage between the enamel (occlusal wall, p>0.05) and dentin (gingival wall, p>0.05) margins among the understudy groups. Conclusion: The degree of marginal microleakage in soft-start (SS) polymerization was not significantly different from that in conventional and pulse polymerizations of class V composite restorations